Fractional time delay estimation method based on the minimum CIM and the Farrow structure - ULing Y; IUTian-shuang Q (Tongxin xuebao)
A fractional time delay estimation algorithm is proposed which is based on the minimum CIM and the Farrow structure (referred to as MCIMFarrow).The proposed MCIMFarrow algorithm performs well in symmetric Alpha stable noise conditions.And it needs little observation data to gain high accuracy estimation results.The theoretical analyses and the simulation results show that the MCIMFarrow is much better than the LETDE algorithm based on the fractional lower order moments in the accuracy of the time delay estimation and the robustness in impulsive noise conditions.